Desindustrialização no Brasil: uma análise estrutural - Rossi, Caroline Gut (2015)
The Brazilian industry has become in recent decades, which created an intense debate about a possible process of deindustrialization faced by the Brazilian economy. Some authors believe that the country has faced a process of deindustrialization, while others argue that this is just a period of adjustment faced by the economy, which does not characterize this fact. The fall of the Manufacturing Industry's participation in the Gross Domestic Product of the country, coupled with the increase in exports of commodities by Brazil are among the main factors that lead to believe that the country has lost links in the production chain and specializing in goods with little degree of differentiation. In this context, this paper aims to analyze the main data of the Brazilian industry to identify the process of deindustrialization pointed in Brazil. We wanted to understand what the main lines of argument in the debate on the subject, and understand how they behaved the main economic aggregates of the country and other economies in the world, producing a structural analysis on the subject.